Modelling of microturbine generation system using matlab/simulink / Khairul Raffiq Mansor - Mansor, Khairul Raffiq (2009)
Microturbine is one of the Distributed Generation (DG). DG resource is small ranging about ten kW to fractional of MW. Nowadays, enhancement in technology of microturbine has become most promising technologies for small modular installation because desired features such as simplicity in mechanism, compact size, light weight, low emission and ability to operate with a wide range of fuels, as well as combined heat and power possibilities. In order to understand the microturbine's operation, their efficiency model is required. This thesis presents the modelling of microturbine generation system using MATLAB/SIMULINK. Dynamic simulation model of a microturbine was conducted by implementing the SimPowerSystem in MATLAB/SIMULINK. Each component in the microturbine is represented by mathematical model. By using the model, signal analysis is conducted during start-up of the model. The model is conducted in grid-connected mode and islanded mode. The simulation shows the operation of microturbine in both modes.